Perencanaan Keuangan untuk Mengurangi Risiko Kebangkrutan : Pentingnya Pengelolaan Keuangan, Pencatatan yang Baik, dan Strategi Pengelolaan Arus Kas: (Studi kasus Rumah Makan Fajar Jeumpa) - Fahmi Fauzi; Aida Ulviani Nst; Layyinatus Shifah; Sugianto Sugianto (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Bankruptcy is one of the main threats to business sustainability, especially for micro, small, and medium enterprises (MSMEs). This article explores the importance of financial planning, accurate record-keeping, and cash flow management strategies to mitigate bankruptcy risks, focusing on a case study of Rumah Makan Fajar Jeumpa. The findings reveal that irregular transaction recording, ineffective cash flow management, and the absence of structured financial strategies are key factors contributing to financial vulnerability. By implementing simple financial record-keeping systems, creating budget projections, and diversifying income sources, MSMEs can enhance operational stability and reduce financial risks. These findings emphasize that comprehensive financial planning, supported by adequate financial literacy, is crucial in ensuring business sustainability and fostering MSME growth.